1992
DOI: 10.7326/0003-4819-117-3-234
|View full text |Cite
|
Sign up to set email alerts
|

Cough and Angioneurotic Edema Associated with Angiotensin-Converting Enzyme Inhibitor Therapy

Abstract: Cough occurs in 5% to 20% of patients treated with ACE inhibitors, recurring with reintroduction of the same or another ACE inhibitor. It is more common in women. The mechanism may involve accumulation of prostaglandins, kinins (such as bradykinin), or substance P (neurotransmitter present in respiratory tract C-fibers); both bradykinin and substance P are degraded by ACE. A 4-day trial of withdrawal of the ACE inhibitor or temporary substitution of another class of antihypertensive agent inexpensively and eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
516
2
27

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 866 publications
(563 citation statements)
references
References 160 publications
18
516
2
27
Order By: Relevance
“…This study was not designed to specifically compare the incidence of cough. Results of other studies have shown that treatment with ACE inhibitors is associated with increased incidence of cough [11][12][13] whereas treatment with AII receptor antagonists is not. 18,19 The overall database incidence of cough is 2.7% for placebo and 2.8% for irbesartan (Data on file, Bristol-Myers Squibb).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was not designed to specifically compare the incidence of cough. Results of other studies have shown that treatment with ACE inhibitors is associated with increased incidence of cough [11][12][13] whereas treatment with AII receptor antagonists is not. 18,19 The overall database incidence of cough is 2.7% for placebo and 2.8% for irbesartan (Data on file, Bristol-Myers Squibb).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because ACE is also involved in the breakdown of bradykinin, inhibition of ACE tends to increase circulating levels of this peptide, [8][9][10] which may account for the increased incidence of cough reported in up to 20% of patients treated with ACE inhibitors. [11][12][13] All receptor antagonists, however, inhibit the potent pressor effect of AII by blocking its binding to the receptor. Therefore, it is expected that they will effectively lower systemic blood pressure without inducing adverse effects, such as cough, that are associated with ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] First dose hypotension is uncommon (except in salt-and/or volume-depleted patients). Cough, the main adverse effect of ACE inhibitors, 111 occurs much less frequently with ARB therapy, and angioneurotic oedema is relatively rare. [112][113][114][115][116] Pharmacokinetics and metabolism of angiotensin receptor blockers Candesartan cilexetil: Candesartan cilexetil, an inactive racemic prodrug, is rapidly and completely metabolised (by ester hydrolysis) in the gastrointestinal tract to the active achiral candesartan.…”
Section: Adverse Effects Of Angiotensin Receptor Blockersmentioning
confidence: 99%
“…1,2 However, inhibition of the converting enzyme has effects beyond the RAS and results in well recognised sideeffects associated with this class of agents including cough and angioneurotic oedema. These side-effects are thought to be due to the accumulation of other substrates of the converting enzyme such as bradykinin and substance P. 3,4 Selective inhibition of the RAS at a more distal level would be anticipated to result in effective antihypertensive agents devoid of these unwanted effects. Angiotensin II antagonists, also known as angiotensin II receptor blockers, have a novel mechanism of action and have been reported to effectively lower blood pressure without cough as a side effect.…”
Section: Introductionmentioning
confidence: 99%